Effects of ammonia on different biological 15 traits of the orange mud crab (Scylla olivacea) - Muhammad, Shoaib; Akram, Wasim; Aziz, Dania; Rahi, Md. Lifat (Scopes Science, 2023)
The orange mud crab (Scylla olivacea) is currently one of the most emerging crustacean species for coastal aquaculture, particularly in the Asian region. This species is sensitive to various aspects of water quality parameters. Ammonia is considered as one of the most common pollutants in crab farms that adversely affect overall production. Therefore, the present study observed the effects of different experimental doses of ammonia (0PPM, 5 PPM and 10 PPM) to investigate the effects of ammonia on various aspects of cellular, physiological, biochemical and genetic alterations in the orange mud crab (Scylla olivacea). Significantly lower hemocyte counts were observed for the 5 PPM and 10 PPM ammonia treatments compared to the control group while no significant difference was detected between the two treatment groups. Ammonia treatments significantly altered expression pattern of the selected set of candidate genes. The ± amylase (growth gene) showed reduced expression (1.5“2 fold lower) in treatments while Toll like receptor (immune response gene) and Acetyl-CoA Carboxylase (metabolic gene) also showed significantly lower expression levels (similar to the levels of ±-amylase) in treatment groups compared to the control. Significantly higher (P < 0.05) and constant rates of O2 consumption in the control group throughout the experiment indicate that these crabs faced no stress and performed faster growth. Therefore, crabs in the control group (0 PPM) showed almost double growth (increase in body weight) compared to treatment groups (5 PPM and 10 PPM). Results indicate that different experimental doses of ammonia significantly altered the expression of candidate genes together with changes in physiological (O2 consumption rates, growth), biochemical (total hemocyte counts, glucose and serotonin levels) and cellular (gill ultrastructure) parameters that adversely affected growth and mortality of experimental crabs. Therefore, attempts must be taken to maintain minimum or zero ammonia levels for sustainable mud crab farming across the coastal regions.